Probing nS/nD Rydberg States via 6P3/2 Intermediate Level Using Electromagnetically Induced Transparency in 87Rb - Donghao Li; Beining Xu; Keyu Qin; Xin Jia; Changtao Zhao; Yaoting Zhou; Zhongxiao Xu (Photonics)
We perform precise measurements of the 87Rb Rydberg excitation spectrum by using electromagnetically induced transparency (EIT) in a ladder system. We utilize a two-photon excitation configuration with the probe and control lasers at 420 nm and 1013 nm, respectively. In this work, we employ <semantics>6P3/2,</semantics>F′ = 3 as an intermediate state to excite the high-lying Rydberg states of the <semantics>nS</semantics> and <semantics>nD</semantics> series, with principal quantum numbers ranging from <semantics>n=35</semantics> to <semantics>n=70</semantics>. To improve the signal-to-noise ratio (SNR) in this inverted level scheme (<semantics>λp<λc</semantics>), we apply a 100 kHz chopping to the control beam, which is followed by a demodulation operated with a lock-in amplifier. Additionally, we verify the ionization energies and determine the quantum defects for the <semantics>nS</semantics> and <semantics>nD</semantics> series, respectively. Our work offers a database for applications of large-scale quantum simulation and quantum computation with the 87Rb atom array.